PENINGKATAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA MELALUI PEMBELAJARAN DISCOVERY LEARNING BERBASIS “GALERY WALK” DENGAN PENDEKATAN CRT - Nabila, Risvya Faiz; Susanti, Vera Dewi; Nartini, Nartini (FIBONACCI: Jurnal Pendidikan Matematika dan Matematika, 2024)
This study aims to improve students' mathematical communication skills through the application of the Discovery Learning learning model combined with Gallery Walk and the Culturally Responsive Teaching (CRT) approach to class IX A students of SMPN 1 Madiun. The study was conducted using the Classroom Action Research (CAR) method in two cycles, which included planning, implementation, observation, and reflection. Data collection was carried out through observation and mathematical communication skills tests. The results of the study showed a significant increase in students' mathematical communication skills. The average score of students increased from 63.69 in the pre-cycle, to 75.72 in cycle I, and 86.75 in cycle II. The percentage of students who achieved the Minimum Completion Criteria (KKM) also increased, from 31.25% in the pre-cycle, to 59.38% in cycle I, and 84.38% in cycle II. Several obstacles, such as limited classroom space and the scope of integrated cultures, were successfully overcome by learning outside the classroom and expanding the cultural context. This study proves that the Discovery Learning learning model based on Gallery Walk with the CRT approach is effective in improving students' mathematical communication skills.